2016
DOI: 10.1007/s12671-016-0558-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Spanish Version of the Nonattachment Scale (NAS) and Its Relationship with Mindfulness, Decentering, and Mental Health

Abstract: Nonattachment is a Buddhism-rooted construct, which can be defined as the relative absence of fixation on ideas, images, or sensory objects, as well as an absence of internal pressure to get, hold, avoid, or change circumstances or experiences. The present study was aimed at exploring the psychometric properties of the Spanish version of the Nonattachment Scale (NAS) and at delimitating the relationship between the NAS and measures of mindfulness, decentering, and negative emotional symptoms. Pooling the NAS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…We did not find this kind of association in our study, but we observed that the higher the basal levels for non-attachment, and the higher the improvement in this variable by means of meditative practice, the greater the benefits it might bring. We found that both retreatants and controls had similar non-attachment scores at baseline (similar to other samples of meditators) (Feliu-Soler et al, 2016), and the retreat was able to increase non-attachment by almost double in comparison with the control group, in terms of the increment. Therefore, this variable, to some extent, may have a ceiling effect when practiced in a non-intensive way.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We did not find this kind of association in our study, but we observed that the higher the basal levels for non-attachment, and the higher the improvement in this variable by means of meditative practice, the greater the benefits it might bring. We found that both retreatants and controls had similar non-attachment scores at baseline (similar to other samples of meditators) (Feliu-Soler et al, 2016), and the retreat was able to increase non-attachment by almost double in comparison with the control group, in terms of the increment. Therefore, this variable, to some extent, may have a ceiling effect when practiced in a non-intensive way.…”
Section: Discussionsupporting
confidence: 87%
“…Evidence consistent with Buddhist theory has demonstrated that non-attachment is psychologically and socially adaptive. We used a Spanish validated version with adequate properties in meditators (α = 0.95) and non-meditators (α = 0.94) (Feliu-Soler et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Some SG‐MBIs also introduce participants to meditative concepts such as impermanence, interconnectedness, non‐self or emptiness, and non‐attachment (Shonin & Van Gordon, ). The introduction of the non‐attachment principle is based on the Buddhist view that suffering arises as a result of an individual's ‘attachment’ to both themselves and external phenomena (e.g., wealth, people, and reputation; Feliu‐Soler et al ., ). The Buddhist notion of attachment has been defined as ‘the over‐allocation of cognitive and emotional resources towards a particular object, construct, or idea to the extent that the object is assigned an attractive quality that is unrealistic and that exceeds its intrinsic worth’ (Shonin, Van Gordon, & Griffiths, , p. 126).…”
Section: Introductionmentioning
confidence: 97%
“…wealth, people, reputation, etc. ; Feliu-Soler et al 2016). The Buddhist notion of attachment has been defined as “the over-allocation of cognitive and emotional resources towards a particular object, construct, or idea to the extent that the object is assigned an attractive quality that is unrealistic and that exceeds its intrinsic worth” (Shonin et al 2014, p. 126).…”
Section: Introductionmentioning
confidence: 99%